A Spiritual Prescription for the Sick - Khalid Hussain; Hüseyin Çaksen (Maklumat: Journal of Da'wah and Islamic Studies, 2026)
This review examines Message for the Sick, drawn from the Twenty-Fifth Flash of Said Nursi’s Risale-i Nur, highlighting its theological depth and pastoral sensitivity. Nursi reframes illness as spiritually meaningful states rooted in divine wisdom, presenting suffering not as punishment but as a pathway to understanding God’s attributes. His remedies for the sick offer a Qur’an-centred lens through which vulnerability becomes a source of insight, patience, and inner transformation. Through close textual analysis, this review demonstrates how Nursi’s reflections integrate Islamic spirituality, ethical psychology, and metaphysical reasoning. The treatise ultimately provides a holistic and timeless model of spiritual care relevant for clinicians, caregivers, and readers seeking to understand hardship through faith.